Combination Vaccination With Tetanus Toxoid and Enhanced Tumor-Cell Based Vaccine Against Cervical Cancer in a Mouse Model - Alson, Donia; Schuyler, Scott C.; Yan, Bo-Xin; Samimuthu, Karthika; Qiu, Jiantai Timothy (Frontiers in Immunology, 2020)
Cervical cancer is the fourth most frequent cancer in women with an estimated 530,000 new cases in 2012 representing 7.9% of all female cancers. Approximately 90% of the 270,000 deaths from cervical cancer in 2015 occurred in low-and middle-income countries. In cervical cancers, which is caused by human papillomavirus (HPV) infection, the expression of HPV 16 E6 and E7 proteins are essential for tumor cell transformation and maintenance of malignancy. Prophylactic vaccines against cervical cancer caused by human papillomavirus have not proven successful. Although virus-like particle-based (VLPs) vaccines have been developed with prophylactic activities to prevent most HPV infections, the therapeutic effect of VLP vaccines has yet to be demonstrated for those who were already infected. A recent study showed that pre-conditioning mice with a potent antigen such as tetanus toxoid significantly improves lymph node homing and efficacy of dendritic cells. Tetanus toxoid has also been used in combination with DNA vaccines designed from tumor based antigens. In the present study, we pre-conditioned mice with tetanus toxoid followed by vaccination with a Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) overexpressing tumor-cell based vaccine (GVAX). We observed that pre-conditioning with tetanus toxoid followed by vaccination with GVAX regressed tumor growth and enhanced the overall survival of the mice. Preconditioning with tetanus toxoid enhanced the immune response which was observed by enlarged spleen size, higher proliferation rate of lymphocytes, a higher level of IFN-γ, TNF-α, and IL-4 antigen-specific secretions by the splenocytes. Pre-conditioning with tetanus toxoid increased memory T cell migration into the tumor site and spleen. The 2 of antigen-specific cytotoxic T cell lysis percentage was also found to be higher in the group of mice vaccinated with the combination of tetanus toxoid and GVAX. Hence, preconditioning with tetanus toxoid prior to vaccination with a tumor-cell based vaccine overexpressing GM-CSF might be an effective strategy for targeting E7-specific HPVassociated cervical malignancy.